2022
DOI: 10.3758/s13423-022-02149-2
|View full text |Cite
|
Sign up to set email alerts
|

Does taking multiple photos lead to a photo-taking-impairment effect?

Abstract: The photo-taking-impairment effect is observed when photographed information is less likely to be remembered than nonphotographed information. Three experiments examined whether this effect persists when multiple photos are taken. Experiment 1 used a within-subjects laboratory-based design in which participants viewed images of paintings and were instructed to photograph them once, five times, or not at all. Participants' memory was measured using a visual detail test, and the photo-taking-impairment effect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Indeed, photo‐taking goals could help elucidate the mixed literature examining photo‐taking effects on memory. Some studies have indicated that photo‐taking can impair memory for photographed information (Henkel, 2014; Lurie & Westerman, 2021; Soares & Storm, 2018, 2022b), while others have found the opposite effect: that photo taking benefits memory for photographed information (Barasch et al, 2017; Ditta et al, 2023). It is possible that taking photos with different goals in mind or in different situations could trigger different cognitive processes and result in different memory effects of photo taking.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, photo‐taking goals could help elucidate the mixed literature examining photo‐taking effects on memory. Some studies have indicated that photo‐taking can impair memory for photographed information (Henkel, 2014; Lurie & Westerman, 2021; Soares & Storm, 2018, 2022b), while others have found the opposite effect: that photo taking benefits memory for photographed information (Barasch et al, 2017; Ditta et al, 2023). It is possible that taking photos with different goals in mind or in different situations could trigger different cognitive processes and result in different memory effects of photo taking.…”
Section: Discussionmentioning
confidence: 99%
“…Esses autores argumentam que o direcionamento no desenho do experimento de Henkel teria influenciado os resultados, pois as pessoas voluntariamente tirariam fotos envolvendo objetivos e processos atencionais não examinados na pesquisa anterior (Barasch et al, 2017). Ainda que pesquisas posteriores tenham confirmado de algum modo o efeito relatado (Soares & Storm, 2022;Lurie & Westerman, 2021;Soares & Storm, 2018;Niforatos et al, 2017), a preocupação com o desenho de pesquisa levantada por Barasch et al (2017) tem sido sempre discutida (Soares & Storm, 2022).…”
Section: O Problema: Pontos Críticos Do Efeito Photo-takingimpairmentunclassified
“…A descarga cognitiva, discutida por Henkel e apoiada em Sparrow et al (2011), sugere que os participantes tiveram uma perda em sua atenção porque passariam a confiar na memória externa da câmera. Por outro lado, o desengajamento atencional estaria relacionado com a dupla tarefa de usar uma câmera (Soares & Storm, 2018), onde o prejuízo de memória teria relação com uma desconexão da cena, impedindo os participantes de codificar o objeto observado (Soares & Storm, 2022). Soares e Storm (2022), mais recentemente, com novos experimentos, alegam ter encontrado evidências mais convincentes contra a hipótese da descarga cognitiva.…”
Section: O Problema: Pontos Críticos Do Efeito Photo-takingimpairmentunclassified
“…The existence of such a cognitive offloading relationship is consistent with findings showing memory impairments after saving information externally. Indeed, memory impairments for information saved on a computer (Sparrow et al 2011), information obtained through an internet search (Fisher et al 2021), and photographed information (Henkel 2014; Soares and Storm 2018, 2022a) have been observed relative to memory for information that is not digitally stored. Consistent with this cognitive offloading mechanism, one study showed that participants only experienced memory impairments associated with saving information when they were shown in a practice trial that the saving process was reliable (Schooler and Storm 2021).…”
Section: Photo Age: Temporal Preferences For External Memory Across T...mentioning
confidence: 99%